2016
DOI: 10.18352/ijc.583
|View full text |Cite
|
Sign up to set email alerts
|

Congruence of appropriation and provision in collective water provision in Central Namibia

Abstract: Achieving cooperation in natural resource management is always a challenge when incentives exist for an individual to maximise her short term benefits at the cost of a group. We study a public good social dilemma in water infrastructure provision on land reform farms in Namibia. In the context of the Namibian land reform, arbitrarily mixed groups of livestock farmers have to share the operation and maintenance of water infrastructure. Typically, water is mainly used for livestock production, and livestock numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Partelow 2015, Partelow and Boda 2015, Guevara et al 2016, Oviedo and Bursztyn 2016, Blythe et al 2017, London et al 2017, Nakandakari et al 2017, Partelow et al 2018a) and forestry (Fleischman et al 2010, Oberlack et al 2015, Davenport et al 2016. However, use of the framework has expanded beyond those resource-use sectors to general food production systems (Marshall 2015), aquaculture systems (Partelow et al 2018b), terrestrial conservation and rangeland management (Falk et al 2012, Risvoll et al 2014, Baur and Binder 2015, Addison and Greiner 2016, Taggart-Hodge and Schoon 2016, Yandle et al 2016, Guariguata et al 2017, watershed management (Madrigal et al 2011, Bal et al 2011, Nagendra and Ostrom 2014, Villamayor-Tomas et al 2014, Bennett and Gosnell 2015, Naiga et al 2015, Silva et al 2015, Falk et al 2016, Hileman et al 2016, marine conservation and marine ecosystem management (Cinner et al 2012, Schlüter et al 2013, Stevenson and Tissot 2014, Ban et al 2015, 2017, Williams and Tai 2016, coastal development (Kanwar et al 2016, Schlüter et al 2019, energy systems …”
Section: Trends and Gaps In The Social-ecological Systems Framework Lmentioning
confidence: 99%
“…Partelow 2015, Partelow and Boda 2015, Guevara et al 2016, Oviedo and Bursztyn 2016, Blythe et al 2017, London et al 2017, Nakandakari et al 2017, Partelow et al 2018a) and forestry (Fleischman et al 2010, Oberlack et al 2015, Davenport et al 2016. However, use of the framework has expanded beyond those resource-use sectors to general food production systems (Marshall 2015), aquaculture systems (Partelow et al 2018b), terrestrial conservation and rangeland management (Falk et al 2012, Risvoll et al 2014, Baur and Binder 2015, Addison and Greiner 2016, Taggart-Hodge and Schoon 2016, Yandle et al 2016, Guariguata et al 2017, watershed management (Madrigal et al 2011, Bal et al 2011, Nagendra and Ostrom 2014, Villamayor-Tomas et al 2014, Bennett and Gosnell 2015, Naiga et al 2015, Silva et al 2015, Falk et al 2016, Hileman et al 2016, marine conservation and marine ecosystem management (Cinner et al 2012, Schlüter et al 2013, Stevenson and Tissot 2014, Ban et al 2015, 2017, Williams and Tai 2016, coastal development (Kanwar et al 2016, Schlüter et al 2019, energy systems …”
Section: Trends and Gaps In The Social-ecological Systems Framework Lmentioning
confidence: 99%
“…This second line of experiments more closely aligns with formalizations of the problem (de Janvry et al 1998, Baur andNax 2018) and the experiment reported herein. The main findings are that (i) individuals are willing to make continuously high levels of provision contributions, in spite of being left with fewer resources to harvest because of an unfavorable position, and (ii) individuals with higher appropriation rates compensate with higher contributions in the provision stage (Janssen et al 2011, 2013, Falk et al 2016. These findings point to the existence of a "take more, give more" mechanism in individuals that results in behavioral congruence in joint appropriation-provision situations.…”
Section: Related Experimental Workmentioning
confidence: 88%
“…In property rights' literature, scholars (Bromley 1992;Demsetz 2002;Libecap 2009) reiterate that property rights have to be complete and well-defined regimes for effective natural resource governance. Quinn et al (2007), Falk, Lohmann, and Azebaze (2016), Baggio et al (2016) and Le Tourneau and Beaufort (2017) showed that conformance of natural resource governance arrangements to DP 2 is vital for ensuring sustainable governance of natural resources. "Congruence [to DP 2] seems to be the linchpin for success independent from the type of system" (Baggio et al 2016, 431).…”
Section: Discussionmentioning
confidence: 99%
“…Inability of the local institutions to adequately respond or adapt to changes caused by socio-political instability, localised population growth and demand were cited as other probable reasons for poor adherence to DP 2 (Quinn et al 2007). Similarly, Falk et al (2016) based on their study of collective water provision in Central Namibia, observed norms underpinning congruence between provision and appropriation were more likely to be implicit than explicit in management regimes. For example, they demonstrated the existence of customary norms whereby livestock owners with higher livestock numbers made higher contributions (e.g.…”
Section: Discussionmentioning
confidence: 99%